UJI PENGARUH PESTISIDA NABATI MENGGUNAKAN EKSTRAK DAUN MIMBA (Azadirachta indica) DAN UMBI GADUNG (Dioscorea hispida Dennst.) TERHADAP WALANG SANGIT PADA TANAMAN PADI - Ilmah Noor; Sasi Gendro Sari; Faulina Faulina (Bioscientiae, 2023)
Vegetable pesticides are pesticides whose basic ingredients come from plants. The plants  that can be used  as vegetable pesticides are neem (Azadirachte indica) and Gadung  (Dioscorea  hispida  Dennst.)  plants which contain  active  ingredients  that  can  control  insect  pests. Neem leaves contain active ingredients in the form  of  azadirachtin,  meliantriol,  salanin,  and  nimbin.  Meanwhile,  gadung  tubers are  known  to  contain toxic  active compounds,  namely  dioscorin, diosgenin,  dioscin,  saponins, alkaloids,  and  phenols.  The  purpose of this study was to determine the effectiveness  of  the  effect  of  botanical pesticides  using  extracts  of  neem  leaves and  Gadung  tubers against rice  pests,  namely  Walang Sangit (Leptocorisa  oratorius  F.).  The  method  of application to Walang Sangit was carried out with different concentrations,  namely  40  ml/L,  60  ml/L,  and 80  ml/L. The time of  application of  the  extract  was  carried  out  in  3  treatments,  namely  in  the morning  (08.00  – 10.00  WITA),  in  the  afternoon (11.00  – 12.00 WITA),  and in  the  afternoon  (16.00 – 18.00  WITA).  The  test  results  were  seen  24  hours  after  the application  of  the  extract.  The  results  showed  that  the  concentration  that  had  the  best  results  was  at  a concentration  of  40  ml/liter  which  was  able  to  kill  or  kill  stink  bugs  with a  period  of  48-50  hours.  This  can  be used  as  an alternative  or one of  the recommendations  in controlling  insect  pests,  especially  for  walang  sangit.